Analysis of Rigid Pavement Thickness Using the AASHTO 1993 and MDPJ 2024 Methods - Ramadhani, Amertya; Rizal, Rikki Sofyan (Universitas Ibn Khaldun Bogor, 2026)
Rigid pavement is an important feature of highway infrastructure because it can handle heavy traffic and move it quickly to the subgrade. This study on Section IIB of the Jakarta–Cikampek II South Toll Road Project used two different ways to construct rigid pavement: one that is used all over the world and one that is exclusive to Indonesia. Each approach utilises a different way of analysing that is based on the criteria and conditions of the context in which it is used. The results showed that the first method made a pavement thickness of 28 cm, whereas the second method made a thickness of 29,5 cm. This difference has a big effect on the total cost of building the 13 km toll road segment, which is Rp139.390.857.060,00 for the first method and Rp156.801.134.100,00 for the second. Choosing the ideal design strategy for a pavement solution that is both optimal and long-lasting should take into account local factors, project needs, and cost-effectiveness.